Le vacche e il riso. Analisi di una forma tradizionale di scambio in una società agricola africana - Mizzau, Giorgio (L’Uomo società tradizione sviluppo, 2019)
Economic anthropology has devoted maximum attention to the problem of circulation and has achieved a satisfactory definition of the motivations and means of exchange, but it has not managed to construct a primary theory of value. Among the Diola Bandial rice-growers of Senegal and other nearby ethnic groups, a form of batter has developed in which the Diola Bandial exchange rice for their neighbors' cattle. The problem is to see whether reasons of exchange of these two products can be defined, either in terms of work value or in terms of the law of supply and demand. Setting aside the particular case, which precludes even the calculation of the socially necessary concrete value incorporated in the goods, it can be stated in more general terms that the adjustment of exchange reasons to the relations between values requires the transformation of concrete work into abstract work. Although this transformation is possible in other types of society as well, it can only be achieved automatically in a society based on capitalistic production relationships, by reducing work force to a commodity. But even in the definition of classical economists, the law of value cannot emerge unless there is freedom of action for the supply and demand mechanism. By influencing production, this mechanism alone can eliminate the differences between exchange reasons and relations between values. In the Bandial community, as in all traditional societies, the operation of this balancing mechanism is resisted by strong and rigid pressures, both in the sphere of production and in that of circulation. In the case of the Bandials, moreover, the exchange is directed to the acquisition of prestige goods, that is, goods whose useful value is in a sense artificial and, in any case, can only be judged in relative and not absolute terms. A general decline in the supply of rice (demand for cattle) has not brought about a change in the terms of exchange, because although the individual has fewer cattle in an absolute sense, he still holds the same relative position of prestige vis-à-vis the other members of the community, who also have fewer cattle, and has the same use (prestige) value as before.